2022
DOI: 10.3390/md20100592
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin Production of Microalgae under Different Culture Factors: A Systematic Review

Abstract: Fucoxanthin is one of the light-harvesting pigments in brown microalgae, which is increasingly gaining attention due to its numerous health-promoting properties. Currently, the production of microalgal fucoxanthin is not yet feasible from an economic perspective. However, the cultivation of microalgae at favourable conditions holds great potential to increase the viability of this fucoxanthin source. Hence, this study aimed to review the fucoxanthin production of microalgae under different conditions systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 83 publications
1
35
0
Order By: Relevance
“…When the studies in the literature are examined, it has been reported that the light intensity required for the production of high amounts of fucoxanthin varies between 10 and 100 μmol/m 2 s. Similarly, N. shiloi produced the maximum amount of fucoxanthin at 50 μmol/m 2 s light intensity in this study. Therefore, the obtained result is as expected [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…When the studies in the literature are examined, it has been reported that the light intensity required for the production of high amounts of fucoxanthin varies between 10 and 100 μmol/m 2 s. Similarly, N. shiloi produced the maximum amount of fucoxanthin at 50 μmol/m 2 s light intensity in this study. Therefore, the obtained result is as expected [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…In N. shiloi , low intensities of light caused an increase in the amount of fucoxanthin. Although the adaptability of microalgae to environmental stress, particularly light intensity, is species-specific, there is a similar trend among fucoxanthin-producing microalgae, which states that low light intensity induces a higher accumulation of fucoxanthin [ 32 ]. This increase may be due to the Fucoxanthin–chlorophyll proteins (FCP) which are associated with photosystems (PS) I and II in the thylakoid membranes (TM) in algae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its numerous biological and health-promoting qualities, including its anti-diabetic, anti-obesity, anti-cancer, and antioxidant characteristics, fucoxanthin has received much attention lately ( Muthuirulappan and Francis, 2013 ). The amount of fucoxanthin in microalgae has been shown to grow at light densities between 10 and 100 µmol/m 2 /s; however, the effects of varying light, nutrition, salinity, temperature, and carbon dioxide on fucoxanthin levels vary ( Khaw et al., 2022 ). Therefore, investigations on temperature and salinity are required to achieve the ideal balance between fucoxanthin and biomass production while swiftly putting fucoxanthin into commercial production.…”
Section: Resultsmentioning
confidence: 99%
“…[ 137 ]. Fucoxanthin is the main carotenoid pigment, component of photosynthetic light-harvesting complexes, in marine ecosystems and a member of the xanthophyll family, it can be produced by microalgae and, in particular, Phaeodactilum tricornutum [ 139 ], but it can also be produced in Isochrysis galbana , Odontella sinensis , and Chaetoceros calcitrans [ 140 ]. β-cryptoxanthin is a retinol precursor carotenoid with a chemical structure similar to β-carotene but more polar.…”
Section: Microalgal Molecules With Antioxidant Actionmentioning
confidence: 99%